Sinonim dan Antonim dalam Al-Qur'an - Ridlo, Ubaid (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2017)
Abstract: This article explains the various things about synonyms and antonyms in Arabic linguistic studies. Readers are invited to discuss cross-references on the definition of synonyms and antonyms in the Arabic linguistic context, the background of the emergence of synonyms and antonyms in Arabic, the variety of synonyms and antonyms, and the phenomenon of synonyms and antonyms in the Qur'an. Differences in understanding synonyms and antonyms result in differences in interpreting the Qur'an. Mainstream there are two kinds of pro synonyms and antonyms and counter synonyms and antonyms in the Qur "an. The argument used is the science of linguistics and exegesis, From the pro and contra of this synonym, the concept of partial synonym can be a synthesis in formulating the method of interpretation of the Qur'an. While the antonym in the context of the Qur'anic commentary is one word has two contradictory meanings. Methodology of writing this article is a qualitative approach, with approach of linguistics, and the descriptive analytical method. Keywords:, antonim, al-Quran, fenomena, makna, sinonim